A feasibility study to determine the use of baited pots in Greenland halibut (Reinhardtius hippoglossoides) fisheries, supported by the use of underwater video observations - Folkins,Margaret H.; Grant,Scott M.; Walsh,Philip (PeerJ, 2021)
High incidental catches of Greenland shark (Somniosus microcephalus) in Nunavut’s Greenland halibut (Reinhardtius hippoglossoides) fishery has led to studies on the feasibility of capturing Greenland halibut with baited pots. In this study, catch rates among six experimental pots are compared. In addition to this, underwater video observations of Greenland halibut interacting with two of these experimental pot types are quantified in order to help provide recommendations on future pot designs. Catch rates of Greenland halibut differed among pots with different entrance mesh types, and none of the pots produced substantial amounts of bycatch. Strings of pots were deployed within a narrow corridor between baited gillnets targeting Greenland halibut, which may have affected catch results. Video observations revealed Greenland halibut entangled by their teeth significantly more often in entrance funnels constructed with 50 mm than with 19 mm clear monofilament netting and the entrance rate was 45% higher with the 19 mm netting. Greenland halibut that successfully entered a pot repeatedly became entangled by their teeth in 58 mm netting used in the side and end panels and in a horizontal panel used to separate the pot into a lower and upper chamber. The majority (80%) of Greenland halibut were observed to approach a pot against the current. The downstream entrance was aligned with the current in 52% of the observed Greenland halibut approaches. Seventy percent of entry attempts and 67% of successful entries occurred when fish approached against the current and when the entrance was aligned with the current. These observations lead to recommendations that future studies consider developing a four entrance pot to ensure an entrance is always aligned with bottom currents. Based on these observations of entanglements, it is recommended to use 19 mm clear monofilament netting in the entrance funnel, 100 mm polyethylene netting in the exterior panels, and 19 mm polypropylene netting in the horizontal panel when targeting Greenland halibut. Three Greenland sharks were observed interacting with the pots in the video sets, but none were captured or damaged the pots during the potting experiments, providing validity to the use of pots to mitigate the capture of Greenland shark in Nunavut territorial waters.
Keywords: Greenland halibut; Underwater video; Fishing gear; Behaviour; Nunavut; Sustainability; Conservation; Fisheries